2019
DOI: 10.1001/jamanetworkopen.2019.6412
|View full text |Cite|
|
Sign up to set email alerts
|

Trends in Characteristics, Mortality, and Other Outcomes of Patients With Newly Diagnosed Cirrhosis

Abstract: IMPORTANCE Changes in the characteristics of patients with cirrhosis are likely to affect future outcomes and are important to understand in planning for the care of this population. OBJECTIVE To identify changes in demographic and clinical characteristics and outcomes in patients with newly diagnosed cirrhosis. DESIGN, SETTING, AND PARTICIPANTS A retrospective cohort study of patients with a new diagnosis of cirrhosis was conducted using the Indiana Network for Patient Care, a large statewide regional health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
52
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 43 publications
(97 reference statements)
9
52
2
2
Order By: Relevance
“…Compared to patients without cirrhosis, patients with IC and cirrhosis were more likely to be male, black and Hispanic, although patients in both groups were predominantly White. In contrast, the population of cirrhosis in the USA trends toward male, non-Hispanic blacks and Mexican-Americans, and are of older age [ 17 - 19 ]; however, the population dynamics of cirrhosis continue to change over time, and are expected to continue to do so, as rates of NASH and alcohol-related cirrhosis continue to increase and rates of hepatitis C-related cirrhosis decline [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to patients without cirrhosis, patients with IC and cirrhosis were more likely to be male, black and Hispanic, although patients in both groups were predominantly White. In contrast, the population of cirrhosis in the USA trends toward male, non-Hispanic blacks and Mexican-Americans, and are of older age [ 17 - 19 ]; however, the population dynamics of cirrhosis continue to change over time, and are expected to continue to do so, as rates of NASH and alcohol-related cirrhosis continue to increase and rates of hepatitis C-related cirrhosis decline [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the in-hospital mortality rate of ALD has decreased between 2005–2014, 39 and the mortality rate of ALD cirrhosis has decreased between 2004 and 2014. 40 The cause of the decreased ALD mortality is difficult to ascertain. Nevertheless, our data provide a few hints.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the data may alternatively suggest an increasingly conservative approach to surgery that may potentially be explained by risk aversion attributable to a higher-risk patient population. A statewide population-based study found that new diagnoses of cirrhosis increased by 69% (from 620 to 1045) between 2004 and 2014 [ 12 ], with the greatest increase occurring in patients aged 65 years and older. Over the same time period, a study of 126 Veteran Administration hospitals showed that, while in-hospital mortality decreased from 11.4% to 7.6% among cirrhosis hospitalizations, 30-day post-discharge mortality increased from 9.3% to 10.1% [ 13 ].…”
Section: Discussionmentioning
confidence: 99%